Pengaruh Edukasi Farmasis terhadap Tingkat Kontrol Asma - Sunarti Sunarti; Tri Murti Andayani (Jurnal Farmasi Indonesia, 2015)
One effort to achieve therapeutic success is to improve the control of asthma patients, so that the patient's quality of life is enhanced. The provision of appropriate education and useful by pharmacists is expected to improve asthma control and quality of life better. The purpose of this study was to determine the effect of pharmacist education on the level of asthma control and quality of life of patients with asthma, as well as to determine the correlation level of asthma control and quality of life of asthma patients in the outpatient Center for Public Health Pulmonary Surakarta. Research used experimental design with a control group design with pretest post test. Patients received therapy for asthma were divided into two groups: patients who received education from the researcher (treatment group) and patients without the benefit of education (control group). Data was collected by conducting interviews and questionaires ACT (Asthma Control Test). The amount of test subjects were 77 patients, consisting of 39 treatment group and 38 control group. Analysis of statistical tests used Wilcoxon to see the change in the average scores on the level of asthma control before and after the education of each group, p = 0.000 (Î± <0.05). Mann Whitney test was conducted to determine differences in mean score changes in the level of asthma control in the control group and counselingp = 0.000 (Î± <0.05). This study concluded that education could affect the level of asthma control and quality of life of patients in the education group compared to the control group.